The Periplasmic α-Carbonic Anhydrase Activity of Helicobacter pylori Is Essential for Acid Acclimation - Marcus, Elizabeth A. (American Society for Microbiology, 2005)
The role of the periplasmic α-carbonic anhydrase (α-CA) (HP1186) in acid acclimation of Helicobacter pylori was investigated. Urease and urea influx through UreI have been shown to be essential for gastric colonization and for acid survival in vitro. Intrabacterial urease generation of NH(3) has a major role in regulation of periplasmic pH and inner membrane potential under acidic conditions, allowing adequate bioenergetics for survival and growth. Since α-CA catalyzes the conversion of CO(2) to HCO(3)(−), the role of CO(2) in periplasmic buffering was studied using an α-CA deletion mutant and the CA inhibitor acetazolamide. Western analysis confirmed that α-CA was bound to the inner membrane. Immunoblots and PCR confirmed the absence of the enzyme and the gene in the α-CA knockout. In the mutant or in the presence of acetazolamide, there was an ∼3 log(10) decrease in acid survival. In acid, absence of α-CA activity decreased membrane integrity, as observed using membrane-permeant and -impermeant fluorescent DNA dyes. The increase in membrane potential and cytoplasmic buffering following urea addition to wild-type organisms in acid was absent in the α-CA knockout mutant and in the presence of acetazolamide, although UreI and urease remained fully functional. At low pH, the elevation of cytoplasmic and periplasmic pH with urea was abolished in the absence of α-CA activity. Hence, buffering of the periplasm to a pH consistent with viability depends not only on NH(3) efflux from the cytoplasm but also on the conversion of CO(2), produced by urease, to HCO(3)(−) by the periplasmic α-CA.